Job Satisfaction Reviewed from the Factors of Salary, Work Facilities, and Leadership - Pamungkas, Satrio Aji; Dwiastanti, Anis; Anggoro, Yudhi (Journal of Economic Education and Entrepreneurship Studies, 2025)
The companies strive to achieve their goals through the individuals who are part of them. Having productive, enthusiastic, highly disciplined, and hard-working employees with a strong track record will accelerate the organization's progress toward its goals. In order to create a productive and high-performing workforce, companies need to provide commensurate rewards. Job satisfaction serves as one of the key indicators in measuring the effectiveness of human resource management. This study aims to analyze how salary, work facilities, and leadership are related to job satisfaction. Using quantitative research, data was collected through a questionnaire distributed to 174 employees of PT MIFA Bersama as the research sample. The data was compiled, processed, and analyzed using SPSS to detect relationships through multiple linear regression equations. The results of the study prove that there is a significant relationship between salary, work facilities, and leadership with job satisfaction, both partially and simultaneously. The implications of this study suggest that companies should ensure that their salary system is competitive, always considering industry standards and employee living needs. Management needs to invest in providing comfortable work facilities and training and leadership development activities for managers or supervisors need to be carried out regularly